Fall armyworm infestation, maize production and nutrition security: Evidence from Uganda - Brian Chisanga; Menale Kassie (PLoS ONE, 2025)
We study the impact of fall armyworm (FAW) infestation on nutrition security outcomes in eastern Uganda, measuring nutrition security by dietary diversity scores of vulnerable household members––children under 5 years and their mothers. We use different regression models and aim to take the endogeneity of FAW infestation seriously. We also analyse FAW’s impact pathway to nutrition status and ask whether impacts are caused by reduced maize yields and sales or increased costs associated with insecticide use. The main results are that high FAW infestation reduces maize yields and sales, and adversely affects dietary diversity.